ε-approximate spatial-window aggregation algorithm in wireless sensor networks - Jing GAO; Jian-zhong LI; Yu LIU (Tongxin xuebao)
An efficient ε-approximate spatial-window aggregate query processing technique was proposed to approximate aggregate values over arbitrary regions with arbitrary accuracy.A dynamic programming algorithm was devised to compute minimum number of data to refine approximate summation to reach arbitrary accuracy.The proposed algorithm was efficient to compute minimum/maximum values by only transmitting values promising to be in the exact results in order to reduce energy consumption.The experiment using real-world data demonstrates that the algorithms provide high quality results in arbitrary region and reach arbitrary accuracy with low energy cost.